2022
DOI: 10.1073/pnas.2115669119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism underlying the TLR4 antagonistic and antiseptic activities of papiliocin, an insect innate immune response molecule

Abstract: Significance Similar to mammalian TLR4/MD-2, the Toll9/MD-2–like protein complex in the silkworm, Bombyx mori, acts as an innate pattern-recognition receptor that recognizes lipopolysaccharide (LPS) and induces LPS-stimulated expression of antimicrobial peptides such as cecropins. Here, we report that papiliocin, a cecropin-like insect antimicrobial peptide from the swallowtail butterfly, competitively inhibits the LPS-TLR4/MD-2 interaction by directly binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The host activates the innate and adaptive immune systems by mediating pro-inflammatory cytokines [ 34 ]. However, as the over-activation of pro-inflammatory cytokines leads to multi-organ failure, the initial anti-inflammatory function of macrophages plays a critical role in countering infections [ 35 ]. Hence, we measured the anti-inflammatory activity of rhamnetin after infecting murine macrophages with bacteria that continuously release various pathogen-associated molecular patterns, including LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The host activates the innate and adaptive immune systems by mediating pro-inflammatory cytokines [ 34 ]. However, as the over-activation of pro-inflammatory cytokines leads to multi-organ failure, the initial anti-inflammatory function of macrophages plays a critical role in countering infections [ 35 ]. Hence, we measured the anti-inflammatory activity of rhamnetin after infecting murine macrophages with bacteria that continuously release various pathogen-associated molecular patterns, including LPS.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are widely studied not only for their physiological role in insect immunity, but also for their immunomodulatory characteristics (Hoffmann, 1995;Silvestro et al, 2000;Wu et al, 2018). Krishnan et al, (Krishnan et al, 2022), reported a new molecular mechanism with papiliocin antagonistic effect mediated by its direct binding to the TLR4/MD-2 complex. Such antagonistic effect occurs once peptide competes with LPS for TLR4/MD-2 complex binding site.…”
Section: Figurementioning
confidence: 99%
“…Krishnan et al, ( Krishnan et al, 2022 ), reported a new molecular mechanism with papiliocin antagonistic effect mediated by its direct binding to the TLR4/MD-2 complex. Such antagonistic effect occurs once peptide competes with LPS for TLR4/MD-2 complex binding site.…”
Section: Antimicrobial Peptides Activity On Toll-like Receptormentioning
confidence: 99%
See 2 more Smart Citations